РОЗВИТОК ЗАХВОРЮВАНОСТІ КУРСАНТІВ (Педагогіка вищої та середньої школи, 2009)
The problem of improvement of health in the training of future rescuers for professional activity is viewed, which is connected with the complex of factors of the worsening of young people's health.